OPTIMIZATION OF THREE-DIMENSIONAL MODELING IN ENGINEERING AND BUILDING DESIGN IN THE EDUCATIONAL PROCESS - Krasniuk, A. V.; Tatarinov, O. F.; Ulchenko, T. V. (Science and Transport Progress, 2009)
AutoCAD possibilities of 3D solid modeling are described in the article. The optimum methods of designing for construction and machine drawing applying are analyzed. The choice of methods for 3D solids drawing is proved by samples.